Picture Story Book Analysis of Language Skills at State Kindergarten 1 Selat Penuguan - Erna Budiarti; Widia, Ayu Dwi (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2024)
This study aimed to determine the influence of picture storybooks on children's language skills at TKN 1 Selat Penuguan. This research employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The population for this study comprised all 17 students from Group B at TKN 1 Selat Penuguan. The sampling technique utilized was total sampling, consisting of all 17 TKN 1 Selat Penuguan students. The instrument used in this study was an observation sheet for children's language abilities. In this research, the dependent variable consisted of two variables: before and after. Consequently, a paired sample t-test was conducted to analyze the data using SPSS software. The study's results indicated a significant difference in the mean language ability scores before and after the implementation of picture storybooks, confirming the effectiveness of this learning medium in enhancing children's language development. This study aligns with previous research findings that also discovered a positive correlation between the use of picture storybooks and early childhood language development.